Post-fire recolonisation of a montado area by the endangered Cabrera vole (Microtus cabrerae) (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2007)
The Cabrera vole is an endangered species frequently found in the montado, a savannah-like ecosystem well adapted to fire. Although it is assumed that regular burning is not very prejudicial to this vole, the impact of fire is unknown. This research studied, for the first time, recolonisation by the Cabrera vole after wildfire. Colonies were monitored over one year after a wildfire and the most relevant ecological features in their reestablishment were identified. During the first eight months, all the 18 surveyed colonies remained unoccupied. However, after one year, 11 were recolonised. Vegetation structure and composition in the colonies ( vegetation height, plant families diversity, percentage of bare ground and cover of shrubs before the fire), which are important features in offering protection and nutrition, were closely related to reoccupation of the colonies. Surprisingly, fire intensity did not influence recolonisation. Distance from unburned areas proved to be a factor that delayed recolonisation. The importance of the montado for this species was reinforced by the evidence that recolonisation occurred preferentially in colonies surrounded by this habitat type.